2012
DOI: 10.1248/cpb.c12-00491
|View full text |Cite
|
Sign up to set email alerts
|

Design Space Construction of Multiple Dose-Strength Tablets Utilizing Bayesian Estimation Based on One Set of Design-of-Experiments

Abstract: Design spaces for multiple dose strengths of tablets were constructed using a Bayesian estimation method with one set of design of experiments (DoE) of only the highest dose-strength tablet. The lubricant blending process for theophylline tablets with dose strengths of 100, 50, and 25 mg is used as a model manufacturing process in order to construct design spaces. The DoE was conducted using various Froude numbers (X 1 ) and blending times (X 2 ) for theophylline 100-mg tablet. The response surfaces, design sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…The large-scale acceptance areas calculated by Eqs. 7 and 8 were narrower than the previously-reported acceptance areas 25) calculated by Eqs. 5 and 6 because the small-scale knowledge was downplayed on the improved Bayesian estimation of quality attributes with discrepancy between the manufacturing scales.…”
Section: Estimation Of the Reliability Of The Scale-up Rulecontrasting
confidence: 64%
See 3 more Smart Citations
“…The large-scale acceptance areas calculated by Eqs. 7 and 8 were narrower than the previously-reported acceptance areas 25) calculated by Eqs. 5 and 6 because the small-scale knowledge was downplayed on the improved Bayesian estimation of quality attributes with discrepancy between the manufacturing scales.…”
Section: Estimation Of the Reliability Of The Scale-up Rulecontrasting
confidence: 64%
“…This finding indicated that all the response surfaces had high estimation accuracy because no scale effect was involved. With regard to tablet hardness and dissolution rate, the renewed large-scale design space had higher prediction accuracy than the small-scale and previously-reported large-scale design spaces 25) because of the precise Bayesian estimation and correction of the discrepancy in the quality attributes between the manufacturing scales. We concluded that an accurate large-scale design space can be constructed by Bayesian estimation using the reliabilities of response surface models and scale-up rules without a large-scale DoE study, irrespective of the accuracy of the scale-up rule.…”
Section: Validation Of the Response Surfacesmentioning
confidence: 89%
See 2 more Smart Citations